RAS Mutations and Oncogenesis: Not all RAS Mutations are Created Equally - Miller, Mark S.; Miller, Lance D. (Frontiers in Genetics, 2012)
Mutation in RAS proteins is one of the most common genetic alterations observed in human and experimentally induced rodent cancers. In vivo, oncogenic mutations have been shown to occur at exons 12, 13, and 61, resulting in any one of 19 possible point mutations in a given tumor for a specific RAS isoform. While some studies have suggested a possible role of allele-specific mutation in determining tumor severity and phenotype, no general consensus has emerged on the oncogenicity of different mutant alleles in tumor formation and progression. Part of this may be due to a lack of a single, signature pathway that shows significant alterations between different mutations. Rather, it is likely that subtle differences in the activation, or lack thereof, of downstream effectors by different RAS mutant alleles may determine the eventual outcome in terms of tumor phenotype. This paper reviews our current understanding of the potential role of different RAS mutations on tumorigenesis, highlights studies in model cell culture and in vivo systems, and discusses the potential of expression array and computational network modeling to dissect out differences in activated RAS genes in conferring a transforming phenotype.